2019
DOI: 10.1002/ece3.5715
|View full text |Cite
|
Sign up to set email alerts
|

Warm temperatures during cold season can negatively affect adult survival in an alpine bird

Abstract: Climate seasonality is a predominant constraint on the lifecycles of species in alpine and polar biomes. Assessing the response of these species to climate change thus requires taking into account seasonal constraints on populations. However, interactions between seasonality, weather fluctuations, and population parameters remain poorly explored as they require long‐term studies with high sampling frequency. This study investigated the influence of environmental covariates on the demography of a corvid species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…As in the case of cold‐adapted species (Pearce‐Higgins et al 2015, Scridel et al 2017, Chiffard et al 2019), temperature was found to be among the most important factors influencing the habitat suitability of the alpine specialists of our study; too high temperatures increase physiological stress (Wingfield et al 2011) and reduce reproductive success (Rauter and Reyer 2000, Dreitz et al 2012), but can also cause phenological mismatches between peaks of food availability and energetic demands (Tulp and Schekkerman 2008), and/or increase interspecific competition and predation risk (Jankowski et al 2010, Lurgi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of cold‐adapted species (Pearce‐Higgins et al 2015, Scridel et al 2017, Chiffard et al 2019), temperature was found to be among the most important factors influencing the habitat suitability of the alpine specialists of our study; too high temperatures increase physiological stress (Wingfield et al 2011) and reduce reproductive success (Rauter and Reyer 2000, Dreitz et al 2012), but can also cause phenological mismatches between peaks of food availability and energetic demands (Tulp and Schekkerman 2008), and/or increase interspecific competition and predation risk (Jankowski et al 2010, Lurgi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in seasonal weather patterns and the occurrence of extreme weather events such as droughts, floods, and heatwaves are among the primary drivers of variation in individual success in vertebrates, influencing reproduction and survival both directly and indirectly, often via effects on resource availability (Harrison et al, 2011). To date, most research on the within and between season effects of weather patterns and extreme events has focused on the influence within an annual cycle (Saino et al, 2011;Laplante et al, 2019) of (a) conditions during early development on individual success as a nestling (Pérez et al, 2008;Auer and Martin, 2017;Ospina et al, 2018), fledgling (Blomberg et al, 2014;de Zwaan et al, 2019), or adult (Porcelli et al, 2016;Hsu et al, 2017;Marshall et al, 2017) and (b) seasonal weather conditions on body mass (Loison and Langvatn, 1998;van de Pol et al, 2016), behavior (Akresh et al, 2019;Rauber et al, 2019), survival (Berryman and Lima, 2006;Gardner et al, 2017Gardner et al, , 2018Woodworth et al, 2017;Chiffard et al, 2019), and reproductive investment (Clutton-Brock et al, 1991;Monteuil-Spencer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In high elevation ecosystems, weather conditions may significantly affect several aspect of bird biology. Results of a 27 years demographic research project on marked Alpine Choughs at GM suggested that high winter and spring temperatures may affect spring survival, especially of females (Chiffard et al, 2019). The present study demonstrates that harsh weather conditions may also drive birds' flocking behaviour.…”
Section: Drivers Of the Winter Flocking Behaviour As A Proof Of Conceptmentioning
confidence: 55%
“…The potential foraging advantage of flocking, however, is unclear, because in larger flocks birds feed faster, but stay for a shorter time in patches (Delestrade, 1995;Rolando et al, 1997;Vallino et al, 2019). Recent long term research carried out in the French Alps showed that survival of females decreased with increased flock size, likely because their food provisioning is prevented by males, which are dominant (Chiffard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%